Performance Development Span and Psychological Experience by Stages of Track and Field Athletes - Deok-Hyeon Kim; Young-Kil Yun (Korea Institute of Sport Science, 2023)
PURPOSE The purpose of this study is to section the stages of performance development based on the track and field athletes' performance records, derive the performance development span, which was a continuum of the development stages, and extract the psychological experience of the performance development span. METHODS In this study, 56 retired track and field athletes were provided with competition records, and 10 athletes participated in in-depth interviews. With the stage of performance development partitioned using long and short-term moving averages and regression slope in PRR, a continuous of performance development span was derived. To extract psychological experiences in the performance development span, a subject analysis was conducted after an in-depth interview. RESULTS First, the track and field athletes' performance development stage calculated short and long-term moving averages in the PRR. Based on the average difference in the regression slope of the initial 20% CPR in which the long-term moving average was not calculated, it was divided into beginning, rising, peak, and decline periods. Second, the performance development span was a continuum of the stage was of performance development, and the beginning period was 0 < PRR ≤ 7, it was a time when the competition record rises sharply. The rising period was 7 < PRR ≤ 60, which was a virtuous cycle time of growth athlete. The peak period was 60 < PRR ≤ 74, which was a time when the peak record was maintained. The decline period was 74 < PRR ≤ 100, which was a time when the competition record was downward. Third, throughout the performance development span physical intelligence of track and field athletes was based on their natural physical superiority, the technical skills rises and remains at its peak and then enters a downward trend. Competitional Intelligence aims to become personalization as it matures gradually while its competition management capability and game knowledge are immature. Psychological intelligence overcomes the initial psychological atrophy to form confidence, and after experiencing psychological burden at the peak, confidence decreases. In the environmental context, the competition record rises in the early stages, continues to rise, peaks, and enters a downward trend. CONCLUSIONS Track and field athletes' performance development span was implemented as a continuum of beginning, rising, peak, and decline periods, and the psychological experience of the performance development span formed a span of physical intelligence, competitional intelligence, psychological intelligence, and environmental context.